### (0) Obligation:

JBC Problem based on JBC Program:
Manifest-Version: 1.0 Created-By: 1.6.0_16 (Sun Microsystems Inc.) Main-Class: PastaC2
`/** * Example taken from "A Term Rewriting Approach to the Automated Termination * Analysis of Imperative Programs" (http://www.cs.unm.edu/~spf/papers/2009-02.pdf) * and converted to Java. */public class PastaC2 {    public static void main(String[] args) {        Random.args = args;        int x = Random.random();        while (x >= 0) {            x = x+1;            int y = 1;            while (x >= y) {                y++;            }            x = x-2;        }    }}public class Random {  static String[] args;  static int index = 0;  public static int random() {    String string = args[index];    index++;    return string.length();  }}`

### (1) JBC2FIG (SOUND transformation)

Constructed FIGraph.

### (2) Obligation:

FIGraph based on JBC Program:
PastaC2.main([Ljava/lang/String;)V: Graph of 106 nodes with 1 SCC.

### (3) FIGtoITRSProof (SOUND transformation)

Transformed FIGraph SCCs to IDPs. Logs:

Log for SCC 0:

Generated 27 rules for P and 2 rules for R.

Combined rules. Obtained 2 rules for P and 0 rules for R.

Filtered ground terms:

482_0_main_LT(x1, x2, x3, x4, x5) → 482_0_main_LT(x2, x3, x4, x5)
Cond_482_0_main_LT1(x1, x2, x3, x4, x5, x6) → Cond_482_0_main_LT1(x1, x3, x4, x5, x6)
Cond_482_0_main_LT(x1, x2, x3, x4, x5, x6) → Cond_482_0_main_LT(x1, x3, x4, x5, x6)

Filtered duplicate args:

482_0_main_LT(x1, x2, x3, x4) → 482_0_main_LT(x3, x4)
Cond_482_0_main_LT1(x1, x2, x3, x4, x5) → Cond_482_0_main_LT1(x1, x4, x5)
Cond_482_0_main_LT(x1, x2, x3, x4, x5) → Cond_482_0_main_LT(x1, x4, x5)

Filtered unneeded arguments:

Cond_482_0_main_LT(x1, x2, x3) → Cond_482_0_main_LT(x1, x2)

Combined rules. Obtained 2 rules for P and 0 rules for R.

Finished conversion. Obtained 2 rules for P and 0 rules for R. System has predefined symbols.

### (4) Obligation:

IDP problem:
The following function symbols are pre-defined:
 != ~ Neq: (Integer, Integer) -> Boolean * ~ Mul: (Integer, Integer) -> Integer >= ~ Ge: (Integer, Integer) -> Boolean -1 ~ UnaryMinus: (Integer) -> Integer | ~ Bwor: (Integer, Integer) -> Integer / ~ Div: (Integer, Integer) -> Integer = ~ Eq: (Integer, Integer) -> Boolean ~ Bwxor: (Integer, Integer) -> Integer || ~ Lor: (Boolean, Boolean) -> Boolean ! ~ Lnot: (Boolean) -> Boolean < ~ Lt: (Integer, Integer) -> Boolean - ~ Sub: (Integer, Integer) -> Integer <= ~ Le: (Integer, Integer) -> Boolean > ~ Gt: (Integer, Integer) -> Boolean ~ ~ Bwnot: (Integer) -> Integer % ~ Mod: (Integer, Integer) -> Integer & ~ Bwand: (Integer, Integer) -> Integer + ~ Add: (Integer, Integer) -> Integer && ~ Land: (Boolean, Boolean) -> Boolean

The following domains are used:

Boolean, Integer

R is empty.

The integer pair graph contains the following rules and edges:
(0): 482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(x1[0] > x0[0] && x0[0] > 0 && 0 <= x0[0] - 2, x0[0], x1[0])
(1): COND_482_0_MAIN_LT(TRUE, x0[1], x1[1]) → 482_0_MAIN_LT(x0[1] - 2 + 1, 1)
(2): 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(x1[2] > 0 && x1[2] <= x0[2], x0[2], x1[2])
(3): COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], x1[3] + 1)

(0) -> (1), if ((x1[0] > x0[0] && x0[0] > 0 && 0 <= x0[0] - 2* TRUE)∧(x0[0]* x0[1])∧(x1[0]* x1[1]))

(1) -> (0), if ((x0[1] - 2 + 1* x0[0])∧(1* x1[0]))

(1) -> (2), if ((x0[1] - 2 + 1* x0[2])∧(1* x1[2]))

(2) -> (3), if ((x1[2] > 0 && x1[2] <= x0[2]* TRUE)∧(x0[2]* x0[3])∧(x1[2]* x1[3]))

(3) -> (0), if ((x0[3]* x0[0])∧(x1[3] + 1* x1[0]))

(3) -> (2), if ((x0[3]* x0[2])∧(x1[3] + 1* x1[2]))

The set Q is empty.

### (5) IDPNonInfProof (SOUND transformation)

The constraints were generated the following way:
The DP Problem is simplified using the Induction Calculus [NONINF] with the following steps:
Note that final constraints are written in bold face.

For Pair 482_0_MAIN_LT(x0, x1) → COND_482_0_MAIN_LT(&&(&&(>(x1, x0), >(x0, 0)), <=(0, -(x0, 2))), x0, x1) the following chains were created:
• We consider the chain 482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0]), COND_482_0_MAIN_LT(TRUE, x0[1], x1[1]) → 482_0_MAIN_LT(+(-(x0[1], 2), 1), 1) which results in the following constraint:

(1)    (&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2)))=TRUEx0[0]=x0[1]x1[0]=x1[1]482_0_MAIN_LT(x0[0], x1[0])≥NonInfC∧482_0_MAIN_LT(x0[0], x1[0])≥COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])∧(UIncreasing(COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])), ≥))

We simplified constraint (1) using rules (IV), (IDP_BOOLEAN) which results in the following new constraint:

(2)    (<=(0, -(x0[0], 2))=TRUE>(x1[0], x0[0])=TRUE>(x0[0], 0)=TRUE482_0_MAIN_LT(x0[0], x1[0])≥NonInfC∧482_0_MAIN_LT(x0[0], x1[0])≥COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])∧(UIncreasing(COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])), ≥))

We simplified constraint (2) using rule (POLY_CONSTRAINTS) which results in the following new constraint:

(3)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])), ≥)∧[(-1)bni_17 + (-1)Bound*bni_17] + [bni_17]x0[0] ≥ 0∧[(-1)bso_18] ≥ 0)

We simplified constraint (3) using rule (IDP_POLY_SIMPLIFY) which results in the following new constraint:

(4)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])), ≥)∧[(-1)bni_17 + (-1)Bound*bni_17] + [bni_17]x0[0] ≥ 0∧[(-1)bso_18] ≥ 0)

We simplified constraint (4) using rule (POLY_REMOVE_MIN_MAX) which results in the following new constraint:

(5)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])), ≥)∧[(-1)bni_17 + (-1)Bound*bni_17] + [bni_17]x0[0] ≥ 0∧[(-1)bso_18] ≥ 0)

We simplified constraint (5) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(6)    (x0[0] ≥ 0∧x1[0] + [-3] + [-1]x0[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])), ≥)∧[bni_17 + (-1)Bound*bni_17] + [bni_17]x0[0] ≥ 0∧[(-1)bso_18] ≥ 0)

We simplified constraint (6) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(7)    (x0[0] ≥ 0∧x1[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])), ≥)∧[bni_17 + (-1)Bound*bni_17] + [bni_17]x0[0] ≥ 0∧[(-1)bso_18] ≥ 0)

For Pair COND_482_0_MAIN_LT(TRUE, x0, x1) → 482_0_MAIN_LT(+(-(x0, 2), 1), 1) the following chains were created:
• We consider the chain 482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0]), COND_482_0_MAIN_LT(TRUE, x0[1], x1[1]) → 482_0_MAIN_LT(+(-(x0[1], 2), 1), 1), 482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0]) which results in the following constraint:

(8)    (&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2)))=TRUEx0[0]=x0[1]x1[0]=x1[1]+(-(x0[1], 2), 1)=x0[0]11=x1[0]1COND_482_0_MAIN_LT(TRUE, x0[1], x1[1])≥NonInfC∧COND_482_0_MAIN_LT(TRUE, x0[1], x1[1])≥482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)∧(UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥))

We simplified constraint (8) using rules (III), (IV), (IDP_BOOLEAN) which results in the following new constraint:

(9)    (<=(0, -(x0[0], 2))=TRUE>(x1[0], x0[0])=TRUE>(x0[0], 0)=TRUECOND_482_0_MAIN_LT(TRUE, x0[0], x1[0])≥NonInfC∧COND_482_0_MAIN_LT(TRUE, x0[0], x1[0])≥482_0_MAIN_LT(+(-(x0[0], 2), 1), 1)∧(UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥))

We simplified constraint (9) using rule (POLY_CONSTRAINTS) which results in the following new constraint:

(10)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[(-1)bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

We simplified constraint (10) using rule (IDP_POLY_SIMPLIFY) which results in the following new constraint:

(11)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[(-1)bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

We simplified constraint (11) using rule (POLY_REMOVE_MIN_MAX) which results in the following new constraint:

(12)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[(-1)bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

We simplified constraint (12) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(13)    (x0[0] ≥ 0∧x1[0] + [-3] + [-1]x0[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

We simplified constraint (13) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(14)    (x0[0] ≥ 0∧x1[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

• We consider the chain 482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0]), COND_482_0_MAIN_LT(TRUE, x0[1], x1[1]) → 482_0_MAIN_LT(+(-(x0[1], 2), 1), 1), 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]) which results in the following constraint:

(15)    (&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2)))=TRUEx0[0]=x0[1]x1[0]=x1[1]+(-(x0[1], 2), 1)=x0[2]1=x1[2]COND_482_0_MAIN_LT(TRUE, x0[1], x1[1])≥NonInfC∧COND_482_0_MAIN_LT(TRUE, x0[1], x1[1])≥482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)∧(UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥))

We simplified constraint (15) using rules (III), (IV), (IDP_BOOLEAN) which results in the following new constraint:

(16)    (<=(0, -(x0[0], 2))=TRUE>(x1[0], x0[0])=TRUE>(x0[0], 0)=TRUECOND_482_0_MAIN_LT(TRUE, x0[0], x1[0])≥NonInfC∧COND_482_0_MAIN_LT(TRUE, x0[0], x1[0])≥482_0_MAIN_LT(+(-(x0[0], 2), 1), 1)∧(UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥))

We simplified constraint (16) using rule (POLY_CONSTRAINTS) which results in the following new constraint:

(17)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[(-1)bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

We simplified constraint (17) using rule (IDP_POLY_SIMPLIFY) which results in the following new constraint:

(18)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[(-1)bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

We simplified constraint (18) using rule (POLY_REMOVE_MIN_MAX) which results in the following new constraint:

(19)    (x0[0] + [-2] ≥ 0∧x1[0] + [-1] + [-1]x0[0] ≥ 0∧x0[0] + [-1] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[(-1)bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

We simplified constraint (19) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(20)    (x0[0] ≥ 0∧x1[0] + [-3] + [-1]x0[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

We simplified constraint (20) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(21)    (x0[0] ≥ 0∧x1[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

For Pair 482_0_MAIN_LT(x0, x1) → COND_482_0_MAIN_LT1(&&(>(x1, 0), <=(x1, x0)), x0, x1) the following chains were created:
• We consider the chain 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]), COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1)) which results in the following constraint:

(22)    (&&(>(x1[2], 0), <=(x1[2], x0[2]))=TRUEx0[2]=x0[3]x1[2]=x1[3]482_0_MAIN_LT(x0[2], x1[2])≥NonInfC∧482_0_MAIN_LT(x0[2], x1[2])≥COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])∧(UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥))

We simplified constraint (22) using rules (IV), (IDP_BOOLEAN) which results in the following new constraint:

(23)    (>(x1[2], 0)=TRUE<=(x1[2], x0[2])=TRUE482_0_MAIN_LT(x0[2], x1[2])≥NonInfC∧482_0_MAIN_LT(x0[2], x1[2])≥COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])∧(UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥))

We simplified constraint (23) using rule (POLY_CONSTRAINTS) which results in the following new constraint:

(24)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_21 + (-1)Bound*bni_21] + [bni_21]x0[2] ≥ 0∧[(-1)bso_22] ≥ 0)

We simplified constraint (24) using rule (IDP_POLY_SIMPLIFY) which results in the following new constraint:

(25)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_21 + (-1)Bound*bni_21] + [bni_21]x0[2] ≥ 0∧[(-1)bso_22] ≥ 0)

We simplified constraint (25) using rule (POLY_REMOVE_MIN_MAX) which results in the following new constraint:

(26)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_21 + (-1)Bound*bni_21] + [bni_21]x0[2] ≥ 0∧[(-1)bso_22] ≥ 0)

We simplified constraint (26) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(27)    (x1[2] ≥ 0∧x0[2] + [-1] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_21 + (-1)Bound*bni_21] + [bni_21]x0[2] ≥ 0∧[(-1)bso_22] ≥ 0)

We simplified constraint (27) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(28)    (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)Bound*bni_21] + [bni_21]x1[2] + [bni_21]x0[2] ≥ 0∧[(-1)bso_22] ≥ 0)

For Pair COND_482_0_MAIN_LT1(TRUE, x0, x1) → 482_0_MAIN_LT(x0, +(x1, 1)) the following chains were created:
• We consider the chain 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]), COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1)), 482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0]) which results in the following constraint:

(29)    (&&(>(x1[2], 0), <=(x1[2], x0[2]))=TRUEx0[2]=x0[3]x1[2]=x1[3]x0[3]=x0[0]+(x1[3], 1)=x1[0]COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3])≥NonInfC∧COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3])≥482_0_MAIN_LT(x0[3], +(x1[3], 1))∧(UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥))

We simplified constraint (29) using rules (III), (IV), (IDP_BOOLEAN) which results in the following new constraint:

(30)    (>(x1[2], 0)=TRUE<=(x1[2], x0[2])=TRUECOND_482_0_MAIN_LT1(TRUE, x0[2], x1[2])≥NonInfC∧COND_482_0_MAIN_LT1(TRUE, x0[2], x1[2])≥482_0_MAIN_LT(x0[2], +(x1[2], 1))∧(UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥))

We simplified constraint (30) using rule (POLY_CONSTRAINTS) which results in the following new constraint:

(31)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_23 + (-1)Bound*bni_23] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

We simplified constraint (31) using rule (IDP_POLY_SIMPLIFY) which results in the following new constraint:

(32)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_23 + (-1)Bound*bni_23] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

We simplified constraint (32) using rule (POLY_REMOVE_MIN_MAX) which results in the following new constraint:

(33)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_23 + (-1)Bound*bni_23] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

We simplified constraint (33) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(34)    (x1[2] ≥ 0∧x0[2] + [-1] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_23 + (-1)Bound*bni_23] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

We simplified constraint (34) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(35)    (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)Bound*bni_23] + [bni_23]x1[2] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

• We consider the chain 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]), COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1)), 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]) which results in the following constraint:

(36)    (&&(>(x1[2], 0), <=(x1[2], x0[2]))=TRUEx0[2]=x0[3]x1[2]=x1[3]x0[3]=x0[2]1+(x1[3], 1)=x1[2]1COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3])≥NonInfC∧COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3])≥482_0_MAIN_LT(x0[3], +(x1[3], 1))∧(UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥))

We simplified constraint (36) using rules (III), (IV), (IDP_BOOLEAN) which results in the following new constraint:

(37)    (>(x1[2], 0)=TRUE<=(x1[2], x0[2])=TRUECOND_482_0_MAIN_LT1(TRUE, x0[2], x1[2])≥NonInfC∧COND_482_0_MAIN_LT1(TRUE, x0[2], x1[2])≥482_0_MAIN_LT(x0[2], +(x1[2], 1))∧(UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥))

We simplified constraint (37) using rule (POLY_CONSTRAINTS) which results in the following new constraint:

(38)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_23 + (-1)Bound*bni_23] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

We simplified constraint (38) using rule (IDP_POLY_SIMPLIFY) which results in the following new constraint:

(39)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_23 + (-1)Bound*bni_23] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

We simplified constraint (39) using rule (POLY_REMOVE_MIN_MAX) which results in the following new constraint:

(40)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_23 + (-1)Bound*bni_23] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

We simplified constraint (40) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(41)    (x1[2] ≥ 0∧x0[2] + [-1] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_23 + (-1)Bound*bni_23] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

We simplified constraint (41) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(42)    (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)Bound*bni_23] + [bni_23]x1[2] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

To summarize, we get the following constraints P for the following pairs.
• 482_0_MAIN_LT(x0, x1) → COND_482_0_MAIN_LT(&&(&&(>(x1, x0), >(x0, 0)), <=(0, -(x0, 2))), x0, x1)
• (x0[0] ≥ 0∧x1[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])), ≥)∧[bni_17 + (-1)Bound*bni_17] + [bni_17]x0[0] ≥ 0∧[(-1)bso_18] ≥ 0)

• COND_482_0_MAIN_LT(TRUE, x0, x1) → 482_0_MAIN_LT(+(-(x0, 2), 1), 1)
• (x0[0] ≥ 0∧x1[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)
• (x0[0] ≥ 0∧x1[0] ≥ 0∧[1] + x0[0] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)), ≥)∧[bni_19 + (-1)Bound*bni_19] + [bni_19]x0[0] ≥ 0∧[1 + (-1)bso_20] ≥ 0)

• 482_0_MAIN_LT(x0, x1) → COND_482_0_MAIN_LT1(&&(>(x1, 0), <=(x1, x0)), x0, x1)
• (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)Bound*bni_21] + [bni_21]x1[2] + [bni_21]x0[2] ≥ 0∧[(-1)bso_22] ≥ 0)

• COND_482_0_MAIN_LT1(TRUE, x0, x1) → 482_0_MAIN_LT(x0, +(x1, 1))
• (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)Bound*bni_23] + [bni_23]x1[2] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)
• (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)Bound*bni_23] + [bni_23]x1[2] + [bni_23]x0[2] ≥ 0∧[(-1)bso_24] ≥ 0)

The constraints for P> respective Pbound are constructed from P where we just replace every occurence of "t ≥ s" in P by "t > s" respective "t ≥ c". Here c stands for the fresh constant used for Pbound.
Using the following integer polynomial ordering the resulting constraints can be solved
Polynomial interpretation over integers[POLO]:

POL(TRUE) = 0
POL(FALSE) = 0
POL(482_0_MAIN_LT(x1, x2)) = [-1] + x1
POL(COND_482_0_MAIN_LT(x1, x2, x3)) = [-1] + x2
POL(&&(x1, x2)) = [-1]
POL(>(x1, x2)) = [-1]
POL(0) = 0
POL(<=(x1, x2)) = [-1]
POL(-(x1, x2)) = x1 + [-1]x2
POL(2) = [2]
POL(+(x1, x2)) = x1 + x2
POL(1) = [1]
POL(COND_482_0_MAIN_LT1(x1, x2, x3)) = [-1] + x2

The following pairs are in P>:

COND_482_0_MAIN_LT(TRUE, x0[1], x1[1]) → 482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)

The following pairs are in Pbound:

482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])
COND_482_0_MAIN_LT(TRUE, x0[1], x1[1]) → 482_0_MAIN_LT(+(-(x0[1], 2), 1), 1)
482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])
COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1))

The following pairs are in P:

482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(&&(&&(>(x1[0], x0[0]), >(x0[0], 0)), <=(0, -(x0[0], 2))), x0[0], x1[0])
482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])
COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1))

At least the following rules have been oriented under context sensitive arithmetic replacement:

TRUE1&&(TRUE, TRUE)1
FALSE1&&(TRUE, FALSE)1
FALSE1&&(FALSE, TRUE)1
FALSE1&&(FALSE, FALSE)1

### (6) Obligation:

IDP problem:
The following function symbols are pre-defined:
 != ~ Neq: (Integer, Integer) -> Boolean * ~ Mul: (Integer, Integer) -> Integer >= ~ Ge: (Integer, Integer) -> Boolean -1 ~ UnaryMinus: (Integer) -> Integer | ~ Bwor: (Integer, Integer) -> Integer / ~ Div: (Integer, Integer) -> Integer = ~ Eq: (Integer, Integer) -> Boolean ~ Bwxor: (Integer, Integer) -> Integer || ~ Lor: (Boolean, Boolean) -> Boolean ! ~ Lnot: (Boolean) -> Boolean < ~ Lt: (Integer, Integer) -> Boolean - ~ Sub: (Integer, Integer) -> Integer <= ~ Le: (Integer, Integer) -> Boolean > ~ Gt: (Integer, Integer) -> Boolean ~ ~ Bwnot: (Integer) -> Integer % ~ Mod: (Integer, Integer) -> Integer & ~ Bwand: (Integer, Integer) -> Integer + ~ Add: (Integer, Integer) -> Integer && ~ Land: (Boolean, Boolean) -> Boolean

The following domains are used:

Boolean, Integer

R is empty.

The integer pair graph contains the following rules and edges:
(0): 482_0_MAIN_LT(x0[0], x1[0]) → COND_482_0_MAIN_LT(x1[0] > x0[0] && x0[0] > 0 && 0 <= x0[0] - 2, x0[0], x1[0])
(2): 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(x1[2] > 0 && x1[2] <= x0[2], x0[2], x1[2])
(3): COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], x1[3] + 1)

(3) -> (0), if ((x0[3]* x0[0])∧(x1[3] + 1* x1[0]))

(3) -> (2), if ((x0[3]* x0[2])∧(x1[3] + 1* x1[2]))

(2) -> (3), if ((x1[2] > 0 && x1[2] <= x0[2]* TRUE)∧(x0[2]* x0[3])∧(x1[2]* x1[3]))

The set Q is empty.

### (7) IDependencyGraphProof (EQUIVALENT transformation)

The approximation of the Dependency Graph [LPAR04,FROCOS05,EDGSTAR] contains 1 SCC with 1 less node.

### (8) Obligation:

IDP problem:
The following function symbols are pre-defined:
 != ~ Neq: (Integer, Integer) -> Boolean * ~ Mul: (Integer, Integer) -> Integer >= ~ Ge: (Integer, Integer) -> Boolean -1 ~ UnaryMinus: (Integer) -> Integer | ~ Bwor: (Integer, Integer) -> Integer / ~ Div: (Integer, Integer) -> Integer = ~ Eq: (Integer, Integer) -> Boolean ~ Bwxor: (Integer, Integer) -> Integer || ~ Lor: (Boolean, Boolean) -> Boolean ! ~ Lnot: (Boolean) -> Boolean < ~ Lt: (Integer, Integer) -> Boolean - ~ Sub: (Integer, Integer) -> Integer <= ~ Le: (Integer, Integer) -> Boolean > ~ Gt: (Integer, Integer) -> Boolean ~ ~ Bwnot: (Integer) -> Integer % ~ Mod: (Integer, Integer) -> Integer & ~ Bwand: (Integer, Integer) -> Integer + ~ Add: (Integer, Integer) -> Integer && ~ Land: (Boolean, Boolean) -> Boolean

The following domains are used:

Integer, Boolean

R is empty.

The integer pair graph contains the following rules and edges:
(3): COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], x1[3] + 1)
(2): 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(x1[2] > 0 && x1[2] <= x0[2], x0[2], x1[2])

(3) -> (2), if ((x0[3]* x0[2])∧(x1[3] + 1* x1[2]))

(2) -> (3), if ((x1[2] > 0 && x1[2] <= x0[2]* TRUE)∧(x0[2]* x0[3])∧(x1[2]* x1[3]))

The set Q is empty.

### (9) IDPNonInfProof (SOUND transformation)

The constraints were generated the following way:
The DP Problem is simplified using the Induction Calculus [NONINF] with the following steps:
Note that final constraints are written in bold face.

For Pair COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1)) the following chains were created:
• We consider the chain 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]), COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1)), 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]) which results in the following constraint:

(1)    (&&(>(x1[2], 0), <=(x1[2], x0[2]))=TRUEx0[2]=x0[3]x1[2]=x1[3]x0[3]=x0[2]1+(x1[3], 1)=x1[2]1COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3])≥NonInfC∧COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3])≥482_0_MAIN_LT(x0[3], +(x1[3], 1))∧(UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥))

We simplified constraint (1) using rules (III), (IV), (IDP_BOOLEAN) which results in the following new constraint:

(2)    (>(x1[2], 0)=TRUE<=(x1[2], x0[2])=TRUECOND_482_0_MAIN_LT1(TRUE, x0[2], x1[2])≥NonInfC∧COND_482_0_MAIN_LT1(TRUE, x0[2], x1[2])≥482_0_MAIN_LT(x0[2], +(x1[2], 1))∧(UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥))

We simplified constraint (2) using rule (POLY_CONSTRAINTS) which results in the following new constraint:

(3)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_13 + (-1)Bound*bni_13] + [(-1)bni_13]x1[2] + [bni_13]x0[2] ≥ 0∧[1 + (-1)bso_14] ≥ 0)

We simplified constraint (3) using rule (IDP_POLY_SIMPLIFY) which results in the following new constraint:

(4)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_13 + (-1)Bound*bni_13] + [(-1)bni_13]x1[2] + [bni_13]x0[2] ≥ 0∧[1 + (-1)bso_14] ≥ 0)

We simplified constraint (4) using rule (POLY_REMOVE_MIN_MAX) which results in the following new constraint:

(5)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_13 + (-1)Bound*bni_13] + [(-1)bni_13]x1[2] + [bni_13]x0[2] ≥ 0∧[1 + (-1)bso_14] ≥ 0)

We simplified constraint (5) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(6)    (x1[2] ≥ 0∧x0[2] + [-1] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-2)bni_13 + (-1)Bound*bni_13] + [(-1)bni_13]x1[2] + [bni_13]x0[2] ≥ 0∧[1 + (-1)bso_14] ≥ 0)

We simplified constraint (6) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(7)    (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_13 + (-1)Bound*bni_13] + [bni_13]x0[2] ≥ 0∧[1 + (-1)bso_14] ≥ 0)

For Pair 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]) the following chains were created:
• We consider the chain 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2]), COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1)) which results in the following constraint:

(8)    (&&(>(x1[2], 0), <=(x1[2], x0[2]))=TRUEx0[2]=x0[3]x1[2]=x1[3]482_0_MAIN_LT(x0[2], x1[2])≥NonInfC∧482_0_MAIN_LT(x0[2], x1[2])≥COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])∧(UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥))

We simplified constraint (8) using rules (IV), (IDP_BOOLEAN) which results in the following new constraint:

(9)    (>(x1[2], 0)=TRUE<=(x1[2], x0[2])=TRUE482_0_MAIN_LT(x0[2], x1[2])≥NonInfC∧482_0_MAIN_LT(x0[2], x1[2])≥COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])∧(UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥))

We simplified constraint (9) using rule (POLY_CONSTRAINTS) which results in the following new constraint:

(10)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_15 + (-1)Bound*bni_15] + [(-1)bni_15]x1[2] + [bni_15]x0[2] ≥ 0∧[(-1)bso_16] ≥ 0)

We simplified constraint (10) using rule (IDP_POLY_SIMPLIFY) which results in the following new constraint:

(11)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_15 + (-1)Bound*bni_15] + [(-1)bni_15]x1[2] + [bni_15]x0[2] ≥ 0∧[(-1)bso_16] ≥ 0)

We simplified constraint (11) using rule (POLY_REMOVE_MIN_MAX) which results in the following new constraint:

(12)    (x1[2] + [-1] ≥ 0∧x0[2] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_15 + (-1)Bound*bni_15] + [(-1)bni_15]x1[2] + [bni_15]x0[2] ≥ 0∧[(-1)bso_16] ≥ 0)

We simplified constraint (12) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(13)    (x1[2] ≥ 0∧x0[2] + [-1] + [-1]x1[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-2)bni_15 + (-1)Bound*bni_15] + [(-1)bni_15]x1[2] + [bni_15]x0[2] ≥ 0∧[(-1)bso_16] ≥ 0)

We simplified constraint (13) using rule (IDP_SMT_SPLIT) which results in the following new constraint:

(14)    (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_15 + (-1)Bound*bni_15] + [bni_15]x0[2] ≥ 0∧[(-1)bso_16] ≥ 0)

To summarize, we get the following constraints P for the following pairs.
• COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1))
• (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(482_0_MAIN_LT(x0[3], +(x1[3], 1))), ≥)∧[(-1)bni_13 + (-1)Bound*bni_13] + [bni_13]x0[2] ≥ 0∧[1 + (-1)bso_14] ≥ 0)

• 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])
• (x1[2] ≥ 0∧x0[2] ≥ 0 ⇒ (UIncreasing(COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])), ≥)∧[(-1)bni_15 + (-1)Bound*bni_15] + [bni_15]x0[2] ≥ 0∧[(-1)bso_16] ≥ 0)

The constraints for P> respective Pbound are constructed from P where we just replace every occurence of "t ≥ s" in P by "t > s" respective "t ≥ c". Here c stands for the fresh constant used for Pbound.
Using the following integer polynomial ordering the resulting constraints can be solved
Polynomial interpretation over integers[POLO]:

POL(TRUE) = [1]
POL(FALSE) = [3]
POL(COND_482_0_MAIN_LT1(x1, x2, x3)) = [-1]x3 + x2 + [-1]x1
POL(482_0_MAIN_LT(x1, x2)) = [-1] + [-1]x2 + x1
POL(+(x1, x2)) = x1 + x2
POL(1) = [1]
POL(&&(x1, x2)) = [1]
POL(>(x1, x2)) = [-1]
POL(0) = 0
POL(<=(x1, x2)) = [-1]

The following pairs are in P>:

COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1))

The following pairs are in Pbound:

COND_482_0_MAIN_LT1(TRUE, x0[3], x1[3]) → 482_0_MAIN_LT(x0[3], +(x1[3], 1))
482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])

The following pairs are in P:

482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(&&(>(x1[2], 0), <=(x1[2], x0[2])), x0[2], x1[2])

At least the following rules have been oriented under context sensitive arithmetic replacement:

&&(TRUE, TRUE)1TRUE1
FALSE1&&(TRUE, FALSE)1
FALSE1&&(FALSE, TRUE)1
FALSE1&&(FALSE, FALSE)1

### (10) Obligation:

IDP problem:
The following function symbols are pre-defined:
 != ~ Neq: (Integer, Integer) -> Boolean * ~ Mul: (Integer, Integer) -> Integer >= ~ Ge: (Integer, Integer) -> Boolean -1 ~ UnaryMinus: (Integer) -> Integer | ~ Bwor: (Integer, Integer) -> Integer / ~ Div: (Integer, Integer) -> Integer = ~ Eq: (Integer, Integer) -> Boolean ~ Bwxor: (Integer, Integer) -> Integer || ~ Lor: (Boolean, Boolean) -> Boolean ! ~ Lnot: (Boolean) -> Boolean < ~ Lt: (Integer, Integer) -> Boolean - ~ Sub: (Integer, Integer) -> Integer <= ~ Le: (Integer, Integer) -> Boolean > ~ Gt: (Integer, Integer) -> Boolean ~ ~ Bwnot: (Integer) -> Integer % ~ Mod: (Integer, Integer) -> Integer & ~ Bwand: (Integer, Integer) -> Integer + ~ Add: (Integer, Integer) -> Integer && ~ Land: (Boolean, Boolean) -> Boolean

The following domains are used:

Boolean, Integer

R is empty.

The integer pair graph contains the following rules and edges:
(2): 482_0_MAIN_LT(x0[2], x1[2]) → COND_482_0_MAIN_LT1(x1[2] > 0 && x1[2] <= x0[2], x0[2], x1[2])

The set Q is empty.

### (11) IDependencyGraphProof (EQUIVALENT transformation)

The approximation of the Dependency Graph [LPAR04,FROCOS05,EDGSTAR] contains 0 SCCs with 1 less node.